Power Relationship Marketing dalam Bisnis - Ali Hasan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2017)
Understanding the motivations of consumers to engage in relationships with marketers is important for both practitioners and marketing scholars. To develop an effective theory of relationship marketing, it is necessary to under¬stand what motivates consumers to reduce their available market choices and engage in relational market behaviour by patronizing the same marketer in subsequent choice situations. This article draws on established consumer behaviour literature to suggest that consumers engage in relational marker behaviour due to personal influences, social influences, and institutional influences. Consumers reduce their available choice and engage in relational market behaviour because they want to simplify their buying and consuming tasks, simple information processing, reduce perceived risky, and maintain competitive consistency and a state of psychological comfort. The willingness and ability of both consumers and marketers to engage in relational marketing will lead to greater marketing productivity; unless either consumers or mar¬keters abuse the mutual interdependence and cooperation. This article examines theoretical contributions to a comprehensive relationship marketing concept. In the modern marketing sciences, that interaction in networks of relationships constitutes both the essence of life itself and the essence of society. Marketing just applying the perspective of its own discipline and not properly considering the context within which marketing operates. The article offers an overview of the contributions to relationship marketing from traditional consumer goods marketing, services marketing, business marketing and base theory for research